Mechanics of light-activated self-healing polymer networks. (March 2019) - Yu, Kunhao; Xin, An; Wang, Qiming
Abstract: Optically healable polymers represent an interesting stimuli-responsive self-healing material as the healing process can be controlled on-demand and remotely. The fundamental mechanism of the light-activated interfacial self-healing process has not been theoretically understood. Here, we present a theoretical framework to understand the light-activated interfacial self-healing of soft polymers with light-responsive photophores. We consider that the light propagation through the material matrix triggers the production of free radicals that facilitate the interfacial self-healing process. The self-healing process is considered as a coupled behavior that polymer chains diffuse across the interface and re-form the dynamic bonds assisted by the free radicals. We theoretically relate the light property to the interfacial self-healing strength of the polymers. We predict that the interfacial self-healing strength of the polymer increases with the light illumination time until reaching a plateau. We theoretically explain the effects of the light intensity, light wavelength, and photoinitiator concentration on the self-healing performance. We then apply the theory to two types of soft polymers with inorganic and organic photophores, respectively. The experimentally measured stress–strain behaviors of the original and self-healed samples can be consistently explained by the theory. The experimentally measured relationships between the healing strength and the healing time also agree well with the theoretical results.